PUSAT PENDIDIKAN DAN PELATIHAN DASAR KOPASSUS DENGAN PENERAPAN ARSITEKTUR RAMAH LINGKUNGAN DI BOGOR - Fadhlan Hibatur Rahman; Anggraeni Dyah Sulistiowati (MAESTRO, 2019)
Abstract A place for the Kopassus Basic Education and Training Center in BOGOR, West Java, which aims to shape Indonesian society, especially army forces who want to join into a special army unit, and professionals tasked with protecting and protecting the people and nation, especially Indonesia in all parts of Indonesia. Where the location of the Kopassus Basic Education and Training Center was built in West Java Region precisely in Bogor. The area is very appropriate and strategic due to the lack of special forces education and training centers and in the region the crime rate is very high even the local KAPOLRES records 30 minutes there is 1 case of crime in addition to other places of Education DIKLAT in general. With this Kopassus basic education and training course the opportunity to continue joining a special unit is very easy. And the local community can channel talents and ideals who want to become a professional special force. The Kopassus Education and Training Center building carries the concept of Environmental Friendly Architecture design. The concept of Green Architecture is a concept of Green Architecture, which is also a green architecture, including harmony between humans and their natural environment. Green architecture also contains other dimensions such as time, natural environment, socio-cultural, space, and building techniques. This shows that green architecture is complex, dense and vital compared to architecture in general. . DIKLAT (Education and Training) will look different from other DIKLAT (Education and Training) because this building will provide a friendly building for healthy environments and buildings, in the Kopassus Education and Training Center which has a swimming pool, shooting range, auditorium with the existence of these facility buildings the concept of Environmentally Friendly Architecture is very suitable. Keywords: Kopassus Basic Education and Training Center, at BOGOR West Java, Environmentally Friendly Architecture